1982
DOI: 10.1002/chin.198218283
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: REACTIVITY OF μ‐(η1:η5‐CYCLOPENTADIENYL)‐TRIS(η‐CYCLOPENTADIENYL)DITITANIUM ((μ‐(η1:η5‐C5H4))(η‐C5H5)3TI2) WITH DINITROGEN. STRUCTURE OF A TITANIUM COMPLEX WITH A TRIPLY COORDINATED DINITROGEN LIGAND

Abstract: Der Titelmetallocen‐Komplex (I) zeigt ein stark unterschiedliches Verhalten gegenüber Distickstoff.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…1 The conversion of dinitrogen to ammonia has occupied the attention of inorganic chemists for some time. [6][7][8] Ammonia can be detected upon hydrolysis of reduced titanocene complexes, 9 hydrogenation of a dinuclear zirconium derivative, 10 and protonation of certain molybdenum-and iron-dinitrogen complexes. 11,12 The Chatt cycle refers specifically to the protonation of coordinated molybdenum-and tungsten-dinitrogen complexes and represents an enormous amount of work in attempts to model nitrogenase.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 The conversion of dinitrogen to ammonia has occupied the attention of inorganic chemists for some time. [6][7][8] Ammonia can be detected upon hydrolysis of reduced titanocene complexes, 9 hydrogenation of a dinuclear zirconium derivative, 10 and protonation of certain molybdenum-and iron-dinitrogen complexes. 11,12 The Chatt cycle refers specifically to the protonation of coordinated molybdenum-and tungsten-dinitrogen complexes and represents an enormous amount of work in attempts to model nitrogenase.…”
Section: Introductionmentioning
confidence: 99%
“…The conversion of dinitrogen to ammonia has occupied the attention of inorganic chemists for some time. Ammonia can be detected upon hydrolysis of reduced titanocene complexes, hydrogenation of a dinuclear zirconium derivative, and protonation of certain molybdenum− and iron−dinitrogen complexes. , The Chatt cycle refers specifically to the protonation of coordinated molybdenum− and tungsten−dinitrogen complexes and represents an enormous amount of work in attempts to model nitrogenase. A few years ago, a catalytic variant was reported that takes advantage of the different solubilities of a reducing agent and an acid to slow down a possible side reaction and allow the protonation of coordinated N 2 to produce ammonia catalytically with four turnovers using a soluble molybdenum catalyst .…”
Section: Introductionmentioning
confidence: 99%
“…This coordination mode is rare for a homonuclear species with only three prior reports ( viz . two Ti and one Cu example). IR spectra of a degassed toluene solution of 3 synthesized using 15 N 2 ( 3- 15 N 2 ) remain unchanged before and after exposure to a 14 N 2 atmosphere even after 3 d (Figure S6). Also, N 2 dissociation and reversion to 2 is not observed as Co 3 N 2 L Et/Me is stable to vacuum and storage under Ar.…”
mentioning
confidence: 99%
“…The N–N bond lengths of the two bridging N 2 are 1.175 and 1.178 Å, which are longer than the two terminal N 2 ligands (1.087, 1.051 Å). Compared with dinitrogen-bridged dinuclear complexes, trinuclear complexes with multiple dinitrogen ligands are very rare . When changing the phenyl groups on the phosphorus center in 2a to cyclohexyl groups ( 2b ), dinitrogen-bridged dinuclear complex 3b was generated, probably due to the increase of steric hindrance on the phosphorus center.…”
mentioning
confidence: 99%